Technical Report on a Time-Motion Analysis of Male Judo Cadets’ Combats Between Weight Divisions [Raport Techniczny Z Analizy Czasoworuchowej W Walkach Judo Kadetów Płci Męskiej W Różnych Kategoriach Wagowych] - Aedo-Munoz, E (Idokan Poland Association, 2022)
Methods. Time-motion analysis data of cadet-athletes (age: 15.95 ± 0.68 years-old) were grouped by weight divisions, according to the following criteria: lightweight Lighters (n = 224 combats of -50kg, -55kg and -60kg), middleweight Middlers (n = 76 combats of -66kg, -73kg and -81kg) and heavyweight Heavies (n = 50 combats of -90kg and +90kg) at four state judo championships. Total and sequential time-motion analyses were observed, according to each combat phase (i.e. standing combat, approach, gripping, attack, groundwork combat, and pause phases) and compared by weight divisions, p ≤ 0.05. Results. The main results indicated significant differences between combat time, with lightweight Lighters (234.4s ± 122.3s) > middleweight Middlers (191.6s ± 118.2s) and heavyweight competitors Heavies (176.8s ± 131s), standing combat time, with Lighters (125.4s ± 67.4s) > Middlers (99.6s ± 70.8s) and Heavies (91.1s ± 63.6s), approach phase, with Lighters (41.5s ± 26s) > Middlers (27.2s ± 18.2s) and gripping phase, with Lighters (75.5s ± 49.2s) >Heavies (51.3s ± 36.9s). Conclusions. Our results suggest that individual training programs should be adjusted for cadets according to their weight divisions with consideration given to the temporal structure of the competitive environment. © Idōkan Poland Association